Effects of dietary salbutamol on growth and carcass composition in rainbow trout (Oncorhynchus Mykiss) (Walbaum) : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science (Physiology) at Massey University, Palmerston North, New Zealand - Atapattu, N. S. B. M (Massey University, 2001)
Salbutamol, a β2 adrenergic agonist, has been shown to reduce carcass fat and increase muscle mass and improve feed conversion efficiency in pigs. In the present study, the effects of dietary salbutamol at 20 ppm on growth, feed conversion efficiency, carcass recovery, visceral organ weight, and whole carcass composition of rainbow trout (Oncorhynchus mykiss) were studied. Rainbow trout (eighteen months old; average initial weight 324.0±0.4 g) were fed either the control or control + 20 ppm salbutamol diet for four weeks in a completely randomized design. Fish were weighed at the start and termination of the study, and records of feed intake were maintained. Carcasses were analyzed for protein, fat and ash at the start and completion of the four weeks feeding period. Dietary salbutamol had no adverse effect on fish mortality, health or feed intake. Dietary salbutamol had no effect (p>0.10) on growth, feed intake or feed conversion efficiency of rainbow trout. Internal organ weights such as liver, heart, gonads and viscero-somatic index and hepato-somatic index were also not affected (p>0.10) by dietary salbutamol. Interestingly, kidney weight was significantly (p<0.01) increased by salbutamol. However, it is unlikely that salbutamol directly increased the kidney weight. Increased metabolic load on kidney and blood flow to the kidney could be reasons for increased kidney weight. Although the final weight and the growth rate were not affected by salbutamol, the carcass recovery was significantly higher (p<0.01) in salbutamol treated trout. Whole carcass protein content of both treated and control fish showed no significant differences and clearly reflected the normal allometric growth and body composition. It was concluded that dietary salbutamol at 20 ppm level had no repartitioning effect in growing rainbow trout. The effects of salbutamol at various doses in more mature rainbow trout need to be studied in future studies.
Keywords: Rainbow trout growth; Hormones in animal nutrition